1996
DOI: 10.1016/s0006-3495(96)79477-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of eye lens transparency: light scattering by concentrated solutions of bovine alpha-crystallin proteins

Abstract: Short range order of the crystallins does account for the transparency of the eye lens. To explain the solution structure of this highly concentrated protein solution on a quantitative basis, the hydrodynamic structure and the interparticle interactions of the proteins have to be known. For that purpose, the light scattering of concentrated solutions of alpha-crystallin has been studied. Starting from the detailed knowledge of the solution parameters of alpha-crystallin in diluted solutions, the structure of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…[42][43][44][45][46][47] Much study has been devoted to understanding how the lens remains transparent, despite its high protein concentratons. [42][43][44][45][46][47][48] One factor is avoidance of phase separations within the lens, which would lead to light scattering and opacity, as in cataract formation. The common types of phase separation in protein solutions at high concentration are protein crystal formation and protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45][46][47] Much study has been devoted to understanding how the lens remains transparent, despite its high protein concentratons. [42][43][44][45][46][47][48] One factor is avoidance of phase separations within the lens, which would lead to light scattering and opacity, as in cataract formation. The common types of phase separation in protein solutions at high concentration are protein crystal formation and protein aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…42,43,[47][48][49]58 Both the AP interface and the C-terminal tail interactions observed for the alpha crystallin family exhibit structural polymorphisms (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Although the measurement and analysis of static light scattering of protein solutions has long been a standard method for the characterization of the molar mass and of the self-association of proteins [9], studies of the light scattering of highly concentrated protein solutions [10,11] are quite rare due to technical difficulties associated with sample preparation, conventional techniques of batch measurement, and limitation of conventional analyses to treatment of firstorder deviations from thermodynamic ideality. We have recently presented an extension of multicomponent light scattering theory that is applicable in principle to solutions of multiple species of proteins at arbitrary concentration, taking into account both attractive interactions leading to self-and/or hetero-association, and nonspecific repulsive interactions leading to thermodynamically nonideal behavior [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ␤-and ␥-crystallins have only structural properties (2-4), except that our results showed that ␤A3 crystallin contains proteinase activity (5, 6). The expressions of the crystallins are both developmentally and spatially regulated (1), and their interactions lead to the transparency of the lens because of short range order of the crystallin matrix (7,8).Previous reports have shown that the ␣-crystallin interacts with other crystallins and intermediate filaments (2). An interaction of ␣-crystallin with ␤L-crystallin produced filament-like structures, and similar interactions between ␤L-crystallin with ␣A-crystallin (isolated from UV-A-irradiated lenses) showed even more pronounced filament formation (9).…”
mentioning
confidence: 99%